Sulfation of intrinsic glycoproteins of the rabbit vitreous - Goes, R. M.; Laicine, E. M.; Mendes, MLO; Nader, H. B.; Haddad, A. (Academic Press Ltd, 1998)
The experiments reported here were designed to characterize the intrinsic vitreous glycoproteins and to understand the process of their sulfation. Rabbits were injected intravitreally with S-35-sodium sulfate and killed at several time intervals after injection. In another series of experiments, rabbits were injected either with S-35-sodium sulfate, H-3-fucose or H-3-tyrosine, associated or not associated with tunicamycin administration. Vitreous from the control eyes was also digested with N-glycosidase.. Furthermore, ciliary bodies, the putative source of the intrinsic vitreous glycoproteins, were incubated with S-35-sodium sulfate in the presence or absence of the protein synthesis inhibitor cycloheximide, and the culture media recovered for analysis. These and the vitreous samples of the other experiments were processed for sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and fluorography. Except for serum albumin, practically all polypeptide bands of the vitreous and culture media were labeled with radioactive sulfate and were shown to undergo renewal. The experiments using tunicamycin or enzyme treatment suggest that radioactive sulfate was incorporated not only into the carbohydrate side chains of the glycoproteins but also into the amino acid tyrosine of the polypeptide backbone of these glycoproteins. (C) 1998 Academic Press.
Keywords: protein sulfation; vitreous body; glycoprotein synthesis; proteoglycan